(untitled) (Scientia Agricola, 2020)
Presence of the ALMT1 (aluminum-activated malate transporter) gene confers resistance to aluminum toxicity in Triticum aestivum (common wheat). No resistant cultivars of Triticum turgidum ssp. Durum Desf. (durum wheat) have been registered in Brazil. The aim of this study was to map the ALMT1 through application of the FISH (fluorescence in situ hybridization) technique in five wheat genotypes, common and durum, from the Active Germplasm Bank (AGB) of the Instituto Agronômico (IAC): BH 1146, P19, P33, Anahuac, and IAC 1003. FISH-ALMT1 signals were registered in Anahuac (sensitive) chromosomes and in BH 1146, P19, and P33 (resistant) chromosomes. In the three resistant genotypes, a characteristic double FISH signal was found, located in different chromosomes of the complements: in BH 1146 in chromosome 5D, in P19 in 3B, and in P33 in 6B. This FISH - ALMT1 mapping allows for introgression of aluminum resistance in sensitive cultivars through breeding programs using introgression lines containing these carrier chromosomes.